What active labor market policy works in a recession? - Anders Forslund; Peter Fredriksson; Johan Vikström (Institute for Labour Market Policy Evaluation (IFAU), 2011)
This paper discusses the case for expanding active labor market policy in recession. We find that there is reasonable case for relying more heavily on certain kinds of programs. The argument is tied to the varying size of the lock-in effect in boom and recession. If programs with relatively large lock-in effects should ever be used, they should be used in a downturn. The reason is simply that the cost of forgoing search time is lower in recession. We also provide new evidence on the relative effectiveness of different kinds of programs over the business cycle. In particular we compare an on-the-job training scheme with (traditional) labor market training. We find that labor market training is relatively more effective in recession. This result is consistent with our priors since labor market training features relative large lock-in effects.
Keywords: J08; J64; J68; 330; Active labor market policy; business cycle; unemployment